Tanggung Jawab Korporasi dalam Tindak Pidana Lingkungan Hidup - Ragil Surya Prakasa; Maharani Utami, Maharani Utami; Chesa Wastsaljideri; Viola audra jhunia; Intan Wulan Sari (PUAN INDONESIA, 2024)
The environment has a very important role for the lives of living creatures around it. Therefore, the living environment must always be protected and cared for. In the process of protecting the environment, there are still many people who are irresponsible towards the environment. Not only individuals but also bodies or companies. This study will discuss the responsibilities of corporations or companies in environmental crimes. This study is included in the type of library research, namely research whose object of study uses library data in the form of books as a data source. This study was carried out by reading books, journals, articles and news related to the theme, namely corporate responsibility in environmental crimes. The conclusion of this study is that criminal liability for criminal acts of environmental pollution, the parties that can be held accountable are not only individuals, but also corporations. If the person responsible for the criminal act is the manager or giver of orders in the activities of the corporation, then the manager or giver of orders, in this case an individual, can be sentenced to imprisonment and a fine as a form of legal responsibility. And business entities may be subject to additional penalties in the form of confiscation of profits obtained from criminal acts, closure of all or part of the business premises, repairs resulting from criminal acts, obligation to carry out what was neglected without rights, and placing the company under guardianship.